Contamination of Water Resources by Pesticides - Luísa Faria Monteiro Mazzini; Kassio Ferreira Mendes (Pesticides in Agriculture and Environment, 2021)
Water is one of the most important natural resources for the maintenance of life, being essential its preservation and its quality control. Among the sources of contamination that most affect the environment and water resources, pesticides that are used indiscriminately in agriculture stand out (DELLA-FLORA et al., 2019; REIBER et al., 2020). The use of pesticides in agriculture occurred in the year 1950, in the United States, in what became known as the green revolution, and between 1960 and 1970 this movement was established in Brazil, receiving great fiscal incentive from the government (LOPES and ALBUQUERQUE, 2018). Therefore, the increase in the use of these chemicals has occurred with population growth in recent decades and consequently with the increase in demand for more food products to supply the population (SEVERO et al., 2020). Currently, Brazil is one of the main consumers of pesticides, standing out in the world’s agricultural production (BARRETO et al., 2020). The factors that affect the fate of these products in the environment are the way they are used and handled, the environmental conditions and the physical-chemical properties of pesticides and soil (DELLAMATRICE and MONTEIRO, 2014). In addition, with the removal of riparian forests and with inappropriate soil and crop management, pesticides can be transported to water sources by runoff and/or runin or percolating in the soil profile by leaching, due to rain or irrigation of crops where it was applied (DELLAMATRICE and MONTEIRO, 2014; SEVERO et al., 2020).